Deification or Demonization: Jesus’ Post-Resurrection Body in Luke 24:36-40 - Shannon Dugger (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2022)
There has been much scholarly debate about the mythological category of Jesus, arguing that the Lucan portrayal of his post-resurrection body aligns either with Roman-period beliefs about ghosts or resurrected gods. This paper examines Greco-Roman ghost stories, apotheosis narratives, and academic work from both sides of the debate pertaining to Luke 24:36-401 in an attempt to better understand why the passage resists categorization. The paper also introduces theories of liminality and anomy to explain the possible ambiguity in the gospel’s portrayal of Jesus’ body. The paper concludes that Luke 24 is neither clearly a ghost story nor a deification story. Rather, the overlap in characteristics renders the narrative anomic, perhaps intentionally